2016
DOI: 10.18632/oncotarget.13677
|View full text |Cite
|
Sign up to set email alerts
|

The matricellular protein CYR61 promotes breast cancer lung metastasis by facilitating tumor cell extravasation and suppressing anoikis

Abstract: Matricellular proteins play multiple roles in primary tumor growth, local invasion and tumor angiogenesis. However, their contribution to metastasis and the putative mechanisms involved are less well characterized. In ER-negative human breast cancer, elevated expression levels of the matricellular protein Cysteine-rich angiogenic inducer 61 (CYR61) are associated with more aggressive progression. Here, we investigated the role of CYR61 in breast cancer lung metastasis using the triple negative human breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 55 publications
(63 reference statements)
5
45
0
2
Order By: Relevance
“…As mentioned earlier, Cyr61 overexpression promotes the growth of solid tumors . Our recent study showed that Cyr61 levels are increased in the plasma and BM of patients with ALL, and elevated Cyr61 levels promote cell survival .…”
Section: Discussionsupporting
confidence: 58%
“…As mentioned earlier, Cyr61 overexpression promotes the growth of solid tumors . Our recent study showed that Cyr61 levels are increased in the plasma and BM of patients with ALL, and elevated Cyr61 levels promote cell survival .…”
Section: Discussionsupporting
confidence: 58%
“…Of note, previous studies had reported these genes were associated with cancer cell proliferation. For instance, CYR61 promoted breast cancer lung metastasis by facilitating tumor cell extravasation and suppressing anoikis and PIK3CB was required for the growth of ERBB2 and RAS driven tumors …”
Section: Discussionmentioning
confidence: 99%
“…measured the cell mobility of HT100 cells (attracted to endothelial cells) as 29 ± 4.16 μ m/hour 45 , and Huang et al . reported MDA-MB-231 migration through softer tissues as 37 ± 2.72 μ m/hour 46 .…”
Section: Discussionmentioning
confidence: 99%